2007
DOI: 10.1088/0953-8984/19/22/225006
|View full text |Cite
|
Sign up to set email alerts
|

InAs/GaAs(001) epitaxy: kinetic effects in the two-dimensional to three-dimensional transition

Abstract: Step instability and surface mass transport strongly influence the kinetics of the two- to three-dimensional (2D–3D) transition in InAs/GaAs self-assembly epitaxy. In this paper we report evidence of the step erosion of quantum dots (QDs) nucleated on step edges for samples having different surface morphologies and the explosive nucleation of 3D QDs triggered by it. Related issues such as the temperature dependence of the critical thickness, the volume dependence of the surface mass transport, and the scaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 61 publications
1
25
0
1
Order By: Relevance
“…It has been experimentally found that the nucleation of InAs islands on GaAs(001), above the 1.6 ML critical thickness for the 2D-3D transition, ends within a fraction of a monolayer (≈0.2 ML) [29,30]. Therefore, for the applied growth conditions, the nucleation is sudden and, since the migration length of the adatoms is much larger than the average separation of the nuclei, the probability of two or more adatoms meeting is much smaller than that of the adatoms meeting an existing island.…”
Section: Resultsmentioning
confidence: 99%
“…It has been experimentally found that the nucleation of InAs islands on GaAs(001), above the 1.6 ML critical thickness for the 2D-3D transition, ends within a fraction of a monolayer (≈0.2 ML) [29,30]. Therefore, for the applied growth conditions, the nucleation is sudden and, since the migration length of the adatoms is much larger than the average separation of the nuclei, the probability of two or more adatoms meeting is much smaller than that of the adatoms meeting an existing island.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b shows the photocurrent map recorded under 916 nm illumination. The buried QDs appear as dark areas in the PC-image due to wetting layer thinning [6] around the QDs. The 500x500 nm 2 PC-image was recorded in 10 nm scanning steps.…”
Section: Resultsmentioning
confidence: 99%
“…PbS QDs were synthesized according to Scholes as reported in [4] and mixed with [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) in order to improve charge transport. PbS:PCBM thin films were prepared by spin coating from colloidal solution (40% PbS QDs with 3 nm diameter covered with oleic acid ligands and 12 w/w% PCBM in chlorobenzene) at 8000 rpm onto thin gold electrodes (3nm Cr, 9 nm Au) on a glass slide fabricated by thermal evaporation.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Among the many reconstructions that this surface can present, the As-rich GaAs(001)β2(2 × 4) reconstruction is one of the most popular substrates for growth. Numerous experimental [10][11][12][13][14][15][16][17] and theoretical [18][19][20][21][22] papers have established the unit cell for this reconstruction.…”
Section: Introductionmentioning
confidence: 99%